T Cell Subsets During Early Life and Their Implication in the Treatment of Childhood Acute Lymphoblastic Leukemia - Saghafian-Hedengren, Shanie; Sverremark-Ekström, Eva; Nilsson, Anna (Frontiers in Immunology, 2021)
The immune system plays a major role in recognising and eliminating malignant cells, and this has been exploited in the development of immunotherapies aimed at either activating or reactivating the anti-tumour activity of a patient’s immune system. A wide range of therapeutic approaches involving T lymphocytes, such as programmed cell death protein ligand-1 (PDL-1) inhibitors, cytotoxic T-lymphocyte-associated protein-4 (CTLA-4) blockers, and targeted T-cell therapy through chimeric antigen receptor (CAR)-T cells or bi-specific T-cell engagers, have been introduced to the field of oncology, leading to significant improvements in overall survival of adult cancer patients. During the past few years, the availability and approval T-cell based immunotherapies have become a reality also for the treatment of childhood cancers. However, the distribution, ratio of regulatory to effector cells and the quality of T-cell responses early in life are distinct from those during adolescence and adulthood, raising the possibility that these differences impact the efficacy of immunotherapy. Herein we provide a brief overview of the properties of conventional T cells during early life. Focusing on the most common cancer type during childhood, acute lymphoblastic leukaemia (ALL), we describe how current conventional therapies used against ALL influence the T-cell compartment of small children. We describe early life T-cell responses in relation to immunotherapy and present our opinion that it is not only immaturity of the adaptive immune system, but also the impact of immunosuppression that may prove disadvantageous in the setting of immunotherapies targeting paediatric cancer cells.